Low dielectric loss liquid crystal polymer composite material and preparation method thereof

CN122898153APending Publication Date: 2026-10-13GUANGDONG ZHONGCHENG SPECIAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611189390.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,纯液晶高分子的介电常数通常在3.1至3.3之间,介电损耗角正切值在0.0025至0.0035之间,尚无法完全满足毫米波频段对信号传输低延迟、低损耗的严苛要求

Benefits of technology

本发明液晶高分子复合材料通过改性笼型倍半硅氧烷的分子链末端封端效应与改性六方氮化硼纳米的亚纳米空腔稀释效应的协同作用,在不牺牲加工性和力学强度的前提下,实现了LCP复合材料介电性能与导热性能的同步大幅提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the field of high polymer materials, and discloses a low-dielectric low-loss liquid crystal polymer composite material and a preparation method thereof. The composite material comprises the following raw materials in parts by weight: LCP resin 90-110 parts, modified cage-type silsesquioxane 0.5-1.5 parts, modified hexagonal boron nitride nanosheet 5-7 parts, antioxidant 0.1-0.5 parts, lubricant 0.1-0.5 parts and coupling agent 0.1-0.5 parts. The modified cage-type silsesquioxane is octoamino phenyl POSS surface grafted with fluorinated graphene quantum dots through click chemistry reaction. The modified hexagonal boron nitride nanosheet is a pure-silicon MFI type zeolite nanoslit grown in situ through a hydrothermal method after hydroxylation of a hexagonal boron nitride nanosheet. Through the synergistic effect of the modified cage-type silsesquioxane and the modified hexagonal boron nitride nanosheet, the dielectric property and the heat conduction property of the LCP composite material are greatly improved simultaneously without sacrificing the processability and the mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a low dielectric and low loss liquid crystal polymer composite material and its preparation method. Background Technology

[0002] With the large-scale commercialization of 5G mobile communication technology and the advancement of pre-research on 6G mobile communication technology, the operating frequency of wireless communication systems is rapidly extending from the Sub-6GHz band to the millimeter-wave band. Against this technological backdrop, the dielectric properties of polymer-based composite materials, as high-frequency signal transmission media, have become a key bottleneck restricting system performance. According to electromagnetic wave transmission theory, the propagation delay of a signal in a medium is proportional to the square root of the dielectric constant, while the transmission loss of signal energy is directly related to the dielectric loss tangent. Therefore, for applications such as millimeter-wave antenna substrates and high-frequency flexible circuit boards, the dielectric material must possess a dielectric constant below 3.0 and a dielectric loss tangent below 0.002 at 10GHz, while also maintaining excellent mechanical strength, dimensional stability, heat resistance, and processing performance.

[0003] Thermotropic liquid crystal polymers, due to their rigid rod-like molecular chain structure, can spontaneously orient themselves in the molten state to form a highly ordered liquid crystal phase. They possess intrinsically low dielectric constants, low moisture absorption, and excellent dimensional stability, making them a promising matrix material for high-frequency communications. However, the dielectric constant of pure liquid crystal polymers is typically between 3.1 and 3.3, and the dielectric loss tangent is between 0.0025 and 0.0035, which cannot fully meet the stringent requirements of low delay and low loss signal transmission in the millimeter-wave band. Furthermore, the low thermal conductivity of pure liquid crystal polymers (approximately 0.3 W / m·K) also makes it difficult to address the heat dissipation challenges arising from the increased integration of high-frequency devices. Summary of the Invention

[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide a low-dielectric-loss liquid crystal polymer composite material and its preparation method. Through the synergistic effect of modified cage-type silsesquioxane and modified hexagonal boron nitride nanosheets, the dielectric and thermal conductivity properties of the LCP composite material are simultaneously and significantly improved without sacrificing processability and mechanical strength.

[0005] The objective of this invention can be achieved through the following technical solutions: A low-dielectric-loss, low-loss liquid crystal polymer composite material comprises the following raw materials in parts by weight: 90-110 parts of LCP resin, 0.5-1.5 parts of modified cage-type silsesquioxane, 5-7 parts of modified hexagonal boron nitride nanosheets, 0.1-0.5 parts of antioxidant, 0.1-0.5 parts of lubricant, and 0.1-0.5 parts of coupling agent; The modified cage-like silsesquioxane is an octaaminophenyl POSS surface grafted with fluorinated graphene quantum dots via a click chemical reaction. The modified hexagonal boron nitride nanosheets are pure silicon MFI-type zeolite nanoshuttles grown in situ via hydrothermal method after hydroxylation of hexagonal boron nitride nanosheets.

[0006] Preferably, the LCP resin is a thermotropic aromatic liquid crystal polymer, and the thermotropic aromatic liquid crystal polymer is a copolymer of p-hydroxybenzoic acid, terephthalic acid, or hydroquinone.

[0007] Preferably, the antioxidant is an aromatic phosphite, the lubricant is a hyperbranched polyester polyol, and the coupling agent is an epoxy silane oligomer.

[0008] Preferably, the preparation method of the modified cage-type silsesquioxane includes the following steps: (1) Under ice bath conditions, octaphenyl POSS was slowly added to a mixture of nitric acid and formic acid and stirred at room temperature for 18-22 h. The reaction solution was poured into ice water to precipitate the precipitate. The precipitate was filtered and washed with water until neutral to obtain octanitrophenyl POSS. The obtained octanitrophenyl POSS was then dissolved in tetrahydrofuran, Pd / C catalyst was added, H2 was introduced, and the mixture was stirred at 50 °C for 10-14 h. The Pd / C catalyst was removed by filtration, and the tetrahydrofuran was removed by rotary evaporation of the filtrate to obtain octaaminophenyl POSS. (2) A platinum mesh coated with fluorinated graphite was used as the cathode and a platinum wire as the anode. It was immersed in 100 mL of 0.1 M tetrabutylammonium tetrafluoroborate in acetonitrile solution and a constant potential of -2.5 V to -3.0 V (vsAg / AgCl) was applied for 3 to 5 h until the fluorinated graphite layer separated and the solution turned black. The sloughed suspension was placed in an ice bath and ultrasonically treated for 3 to 5 h. Large particles were first removed by filtration with a 220 nm filter membrane and then dialyzed with a 3500 Da dialysis bag for 46 to 50 h. The filtrate was freeze-dried to obtain fluorinated graphene quantum dots. (3) Fluorinated graphene quantum dots were ultrasonically dispersed in deionized water, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added. The mixture was ultrasonically activated at room temperature for 20-40 min. Octaaminophenyl POSS was dissolved in dimethyl sulfoxide and slowly added dropwise to the above fluorinated graphene quantum dot activation solution. The mixture was protected with N2 and magnetically stirred at 60°C for 22-26 h. After the reaction was completed, the reaction solution was added dropwise to anhydrous ethanol. The precipitate was collected by centrifugation and washed 1-3 times with N,N-dimethylformamide and acetone in sequence. The modified cage-like silsesquioxane was obtained by vacuum drying.

[0009] Preferably, the volume ratio of nitric acid to formic acid in the mixed acid solution is 2:1, and the ratio of octaphenyl POSS to the mixed acid solution is 1g:10~20mL.

[0010] Preferably, the mass ratio of the fluorinated graphene quantum dots, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and octaaminophenyl POSS is 1:0.5:0.3:2.

[0011] Preferably, the preparation method of the modified hexagonal boron nitride nanosheets includes the following steps: A. Add hexagonal boron nitride nanosheets and urea to deionized water, stir evenly, transfer to a planetary ball mill jar and ball mill for 10-14 hours, dilute the ball mill slurry, centrifuge at 1500 r / min at low speed to remove large particles that have not been peeled off, centrifuge the supernatant at 10000 r / min at high speed, collect the bottom precipitate, and freeze dry to obtain hydroxylated hexagonal boron nitride. B. Take hydroxylated hexagonal boron nitride and ultrasonically disperse it in deionized water. Stir tetraethyl orthosilicate, tetrapropylammonium hydroxide aqueous solution, anhydrous ethanol and deionized water to mix evenly to obtain a precursor sol. Slowly drop the prepared precursor sol into the hydroxylated hexagonal boron nitride dispersion and stir and age at room temperature for 4~8 hours. C. The mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner. It was first kept at 80℃ for 22-26 hours, and then the temperature was raised to 170℃ for crystallization for 46-50 hours. After the reactor cooled naturally, the product was washed three times by centrifugation with deionized water, dried at 80℃, and then placed in a muffle furnace and calcined at 550℃ in air for 4-8 hours to obtain modified hexagonal boron nitride nanosheets.

[0012] Preferably, the mass ratio of the hexagonal boron nitride nanosheets to urea is 1:2~3.

[0013] Preferably, the molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide, ethanol and deionized water in the precursor sol is 1:0.35:20:4, and the ratio of hydroxylated hexagonal boron nitride to the precursor sol is 1g:140~160mL.

[0014] A method for preparing a low-dielectric- and low-loss liquid crystal polymer composite material includes the following steps: S1. Modified cage-type silsesquioxane and modified hexagonal boron nitride nanosheets were mixed with LCP ultrafine powder and anhydrous ethanol, respectively, and ball-milled at a low speed of 300 r / min for 2-4 h. The mixtures were then dried to obtain the corresponding pre-dispersions. S2. Premix the two predispersants with LCP resin in a low-speed mixer for 4-6 minutes, add antioxidant, lubricant and coupling agent, and continue mixing until there are no white spots to obtain the mixture. S3. Add the mixture to a twin-screw extruder for melt extrusion. The twin-screw extruder speed is 300~350 r / min, the vacuum degree is -0.08 MPa, and the temperature is 300~330℃. After water cooling and drying, it is cut into cylindrical particles by a pelletizer to obtain modified LCP particles. S4. The modified LCP granules are dried in a dehumidifying dryer at 150℃ for 3~5h, and then injection molded by an injection molding machine with a barrel temperature of 310~330℃, a mold temperature of 120~150℃, a holding pressure of 40~60MPa for 3~5s, and then demolded at 110~120℃ to obtain the low dielectric and low loss liquid crystal polymer composite material.

[0015] The beneficial effects of this invention are: The present invention achieves a simultaneous and significant improvement in the dielectric and thermal conductivity of liquid crystal polymer composite materials without sacrificing processability and mechanical strength through the synergistic effect of the end-capping effect of the molecular chain of modified cage-type silsesquioxane and the sub-nanometer cavity dilution effect of modified hexagonal boron nitride nanoparticles.

[0016] Among them, modified hexagonal boron nitride nanosheets play a role in diluting the dielectric constant and constructing thermally conductive pathways. Regarding reducing the dielectric constant, it utilizes the 0.55 nm subporous structure of the zeolite component to employ size repulsion to keep the liquid crystal polymer macromolecular chains outside the pores, permanently retaining the low-dielectric-constant air gaps, thus reducing the macroscopic dielectric constant of the composite material through a physical dilution mechanism. In terms of improving thermal conductivity, it relies on the excellent two-dimensional lattice phonon transport characteristics of the hexagonal boron nitride component to form an in-plane thermally conductive network penetrating the material through oriented overlap in the injection molding shear flow field, increasing the thermal conductivity by more than four times. Regarding structural stability, the in-situ growth of zeolite on the surface of the boron nitride sheets prevents the re-stacking and agglomeration of the sheets and enhances the efficiency of phonon cross-interface transport by increasing the interfacial area.

[0017] Modified cage-like silsesquioxanes anchor the polar carboxyl and hydroxyl groups at the ends of liquid crystal polymers through the strong electronegativity of the carbon-fluorine bonds at the edges of fluorinated quantum dots, fundamentally severing the secondary dipole relaxation of polar end groups under high-frequency electric fields—a source of loss—and reducing the dielectric loss of the composite material. Simultaneously, the heterogeneous nucleation effect of the cage-like silsesquioxanes induces the liquid crystal polymers to form a more perfect extended-chain crystal structure, improving the tensile strength, modulus, and heat distortion temperature of the material without sacrificing impact toughness. Regarding interface optimization, the organic functional groups in its grafted structure significantly improve the chemical compatibility between the inorganic filler and the organic matrix, effectively eliminating interfacial debonding defects.

[0018] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1

[0021] A modified cage-like silsesquioxane, consisting of 8-aminophenyl POSS surface grafted with fluorinated graphene quantum dots via click chemistry, is prepared by the following steps: (1) Under ice bath conditions, 2.0 g of octaphenyl POSS was slowly added to a mixture of 20 mL nitric acid and 10 mL formic acid and stirred at room temperature for 20 h. The reaction solution was poured into 200 mL of ice water to precipitate the precipitate. The precipitate was filtered and washed with water until neutral to obtain octanitrophenyl POSS. The obtained octanitrophenyl POSS was then dissolved in 50 mL of tetrahydrofuran, 0.2 g of Pd / C catalyst was added, H2 (1.0 MPa) was introduced, and the mixture was stirred at 50 °C for 12 h. The Pd / C catalyst was removed by filtration, and the tetrahydrofuran was removed by rotary evaporation of the filtrate to obtain octaaminophenyl POSS. (2) A platinum mesh coated with fluorinated graphite was used as the cathode and a platinum wire as the anode. It was immersed in 100 mL of 0.1 M tetrabutylammonium tetrafluoroborate in acetonitrile solution and a constant potential of -2.5 V to -3.0 V (vsAg / AgCl) was applied for 4 h until the fluorinated graphite layer separated and the solution turned black. The sloughed suspension was placed in an ice bath and ultrasonically treated for 4 h. Large particles were first removed by filtration with a 220 nm filter membrane and then dialyzed with a 3500 Da dialysis bag for 48 h. The filtrate was freeze-dried to obtain fluorinated graphene quantum dots. (3) 100 mg of fluorinated graphene quantum dots were ultrasonically dispersed in 10 mL of deionized water, 50 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 30 mg of N-hydroxysuccinimide were added, and the mixture was ultrasonically activated at room temperature for 30 min. 200 mg of octaaminophenyl POSS was dissolved in 15 mL of dimethyl sulfoxide and slowly added dropwise to the above fluorinated graphene quantum dot activation solution. The mixture was protected with N2 and magnetically stirred at 60 °C for 24 h. After the reaction was completed, the reaction solution was added dropwise to 200 mL of anhydrous ethanol, and the precipitate was collected by centrifugation. The precipitate was washed twice with N,N-dimethylformamide and acetone, and then vacuum dried to obtain the modified cage-like silsesquioxane.

[0022] Example 2

[0023] A modified hexagonal boron nitride nanosheet is prepared by in-situ growth of pure silicon MFI-type zeolite nanoshuttles via hydrothermal method after hydroxylation of hexagonal boron nitride nanosheets. The preparation method includes the following steps: A. Add 2.0g of hexagonal boron nitride nanosheets and 5.0g of urea to 60mL of deionized water, stir well, transfer to a planetary ball mill jar (100mL zirconia jar, equipped with 50g of 3mm zirconia balls), and ball mill at 500r / min for 12h. After diluting the slurry, centrifuge at 1500r / min for 10min, take the supernatant, then centrifuge the supernatant at 10000r / min for 20min, collect the bottom precipitate, and freeze-dry to obtain hydroxylated hexagonal boron nitride. B. Take 200 mg of hydroxylated hexagonal boron nitride and ultrasonically disperse it in 10 mL of deionized water. Add 10.42 g of tetraethyl orthosilicate, 3.56 g of tetrapropylammonium hydroxide aqueous solution, 12 mL of anhydrous ethanol and 18 mL of deionized water and stir to mix evenly to obtain a precursor sol. Slowly drop the prepared precursor sol into the hydroxylated hexagonal boron nitride dispersion and stir and age at room temperature for 6 h. C. The mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner, kept at 80°C for 24 hours, then heated to 170°C for 48 hours to crystallize. After the reactor cooled naturally, the product was washed three times by centrifugation with deionized water, dried at 80°C, and then placed in a muffle furnace and calcined at 550°C for 6 hours in air atmosphere to obtain modified hexagonal boron nitride nanosheets.

[0024] Example 3

[0025] A low-dielectric-loss, low-loss liquid crystal polymer composite material comprises the following raw materials in parts by weight: 90 parts of hydroquinone copolymer LCP resin, 0.5 parts of modified cage-like silsesquioxane, 5 parts of modified hexagonal boron nitride nanosheets, 0.1 parts of aromatic phosphite, 0.1 parts of hyperbranched polyester polyol, and 0.1 parts of epoxy silane oligomer; wherein the modified cage-like silsesquioxane is prepared in Example 1; and the modified hexagonal boron nitride nanosheets are prepared in Example 2.

[0026] The preparation method of the above-mentioned low-dielectric-loss, low-loss liquid crystal polymer composite material includes the following steps: S1. Modified cage-type silsesquioxane and modified hexagonal boron nitride nanosheets were mixed with LCP ultrafine powder (1% of the total LCP resin) and anhydrous ethanol, respectively, and ball-milled at low speed of 300 r / min for 2 h. The mixtures were then removed and dried to obtain the corresponding pre-dispersions. S2. Premix the two predispersants with LCP resin in a low-speed mixer for 4 minutes, add aromatic phosphite, hyperbranched polyester polyol and epoxy silane oligomer, and continue mixing until there are no white spots to obtain the mixture. S3. Add the mixture to a twin-screw extruder for melt extrusion. The twin-screw extruder speed is 350 r / min, the vacuum degree is -0.08 MPa, and the temperature is 300~330℃. After water cooling and drying, it is cut into cylindrical particles by a pelletizer to obtain modified LCP granules. S4. The modified LCP granules are dried in a dehumidifying dryer at 150℃ for 3 hours, and then injection molded using an injection molding machine with a barrel temperature of 310~330℃, a mold temperature of 120℃, a holding pressure of 40MPa for 5 seconds, and then cooled to 110℃ for demolding to obtain the low dielectric and low loss liquid crystal polymer composite material.

[0027] Example 4

[0028] A low-dielectric-loss, low-loss liquid crystal polymer composite material comprises the following raw materials in parts by weight: 110 parts of terephthalic acid copolymer LCP resin, 1.5 parts of modified cage-like silsesquioxane, 7 parts of modified hexagonal boron nitride nanosheets, 0.5 parts of aromatic phosphite, 0.5 parts of hyperbranched polyester polyol, and 0.5 parts of epoxy silane oligomer; wherein the modified cage-like silsesquioxane is prepared in Example 1; and the modified hexagonal boron nitride nanosheets are prepared in Example 2.

[0029] The preparation method of the above-mentioned low-dielectric-loss, low-loss liquid crystal polymer composite material includes the following steps: S1. Modified cage-type silsesquioxane and modified hexagonal boron nitride nanosheets were mixed with LCP ultrafine powder (1% of the total LCP resin) and anhydrous ethanol, respectively, and ball-milled at low speed of 300 r / min for 4 h. The mixtures were then removed and dried to obtain the corresponding pre-dispersions. S2. Premix the two predispersants with LCP resin in a low-speed mixer for 6 minutes, add aromatic phosphite, hyperbranched polyester polyol and epoxy silane oligomer, and continue mixing until there are no white spots to obtain the mixture. S3. Add the mixture to a twin-screw extruder for melt extrusion. The twin-screw extruder speed is 300 r / min, the vacuum degree is -0.08 MPa, and the temperature is 300~330℃. After water cooling and drying, it is cut into cylindrical particles by a pelletizer to obtain modified LCP particles. S4. The modified LCP granules are dried in a dehumidifying dryer at 150°C for 5 hours, and then injection molded using an injection molding machine. The injection molding machine barrel temperature is 310~330°C, the mold temperature is 150°C, the pressure is held at 60MPa for 3 seconds, and the material is cooled to 120°C for demolding to obtain the low dielectric and low loss liquid crystal polymer composite material.

[0030] Example 5

[0031] A low-dielectric-loss, low-loss liquid crystal polymer composite material comprises the following raw materials in parts by weight: 100 parts of p-hydroxybenzoic acid copolymerized LCP resin, 1 part of modified cage-type silsesquioxane, 6 parts of modified hexagonal boron nitride nanosheets, 0.3 parts of aromatic phosphite, 0.3 parts of hyperbranched polyester polyol, and 0.3 parts of epoxy silane oligomer; wherein the modified cage-type silsesquioxane is prepared in Example 1; and the modified hexagonal boron nitride nanosheets are prepared in Example 2.

[0032] The preparation method of the above-mentioned low-dielectric-loss, low-loss liquid crystal polymer composite material includes the following steps: S1. Modified cage-type silsesquioxane and modified hexagonal boron nitride nanosheets were mixed with LCP ultrafine powder (1% of the total LCP resin) and anhydrous ethanol, respectively, and ball-milled at low speed of 300 r / min for 3 h. The mixtures were then removed and dried to obtain the corresponding pre-dispersions. S2. Premix the two predispersants with LCP resin in a low-speed mixer for 5 minutes, add aromatic phosphite, hyperbranched polyester polyol and epoxy silane oligomer, and continue mixing until there are no white spots to obtain the mixture. S3. Add the mixture to a twin-screw extruder for melt extrusion. The twin-screw extruder speed is 325 r / min, the vacuum degree is -0.08 MPa, and the temperature is 300~330℃. After water cooling and drying, it is cut into cylindrical particles by a pelletizer to obtain modified LCP granules. S4. The modified LCP granules are dried in a dehumidifying dryer at 150°C for 4 hours, and then injection molded using an injection molding machine with a barrel temperature of 310~330°C, a mold temperature of 135°C, a holding pressure of 50MPa for 4 seconds, and then cooled to 115°C for demolding to obtain the low dielectric and low loss liquid crystal polymer composite material.

[0033] Comparative Example 1 A low-dielectric-loss, low-loss liquid crystal polymer composite material comprises the following raw materials in parts by weight: 100 parts of p-hydroxybenzoic acid copolymer LCP resin, 6 parts of modified hexagonal boron nitride nanosheets, 0.3 parts of aromatic phosphite, 0.3 parts of hyperbranched polyester polyol, and 0.3 parts of epoxy silane oligomer; wherein the modified hexagonal boron nitride nanosheets are prepared in Example 2.

[0034] The preparation method of the above-mentioned low dielectric and low loss liquid crystal polymer composite material is the same as that in Example 5, except that the pre-dispersion of cage-type silsesquioxane is not added in claim 2.

[0035] Comparative Example 2 A low dielectric and low loss liquid crystal polymer composite material comprises the following raw materials in parts by weight: 100 parts of p-hydroxybenzoic acid copolymer LCP resin, 1 part of modified cage-type silsesquioxane, 0.3 parts of aromatic phosphite, 0.3 parts of hyperbranched polyester polyol and 0.3 parts of epoxy silane oligomer; wherein the modified cage-type silsesquioxane is prepared in Example 1.

[0036] The preparation method of the above-mentioned low dielectric and low loss liquid crystal polymer composite material is the same as that in Example 5, except that the pre-dispersion of modified hexagonal boron nitride nanosheets is not added in claim 2.

[0037] Performance testing The low dielectric and low loss liquid crystal polymer composite materials prepared in Examples 3-5 and Comparative Examples 1 and 2 were processed into standard samples, and then their dielectric properties, thermal properties, mechanical properties, processing properties and microstructure were tested.

[0038] I. Dielectric Performance Testing Referring to GB / T43801-2024, the dielectric constant (Dk) / dielectric loss (Df) was tested using the split-pillar dielectric resonator method. A 50mm×50mm×1.5mm sample was placed in a split-pillar dielectric resonator fixture, and a vector network analyzer was used to scan the 10GHz frequency point. The frequency deviation of the resonance peak and the change in Q value were recorded, and the software automatically calculated Dk / Df. The sample was then placed in a constant temperature and humidity chamber at 85℃ / 85%RH for 168 hours. After being removed and dried, the dielectric constant (Dk) was immediately tested according to the above method, and the rate of change of Dk after damp heat aging was calculated. The results are shown in Table 1 below.

[0039] Table 1. Test results of dielectric properties of composite materials

[0040] The dielectric constant of Comparative Example 2 is significantly higher than that of Examples 3-5, while that of Comparative Example 1 is comparable to that of the Examples. This indicates that the modified hexagonal boron nitride nanosheets are the key to reducing the dielectric constant, while the modified cage-like silsesquioxane has a limited direct effect on reducing the dielectric constant. The intracrystalline pore size of the pure silicon MFI type zeolite on the surface of the modified hexagonal boron nitride nanosheets of this invention is <1nm, and the radius of gyration of the LCP molecular chain is >2nm. During melt processing, it cannot enter the zeolite pores. Therefore, the zeolite interior permanently retains air-filled sub-nanometer cavities (air Dk≈1.0). According to Lichtenecker's logarithmic mixing law, introducing a low dielectric constant phase (air) can effectively reduce the macroscopic dielectric constant of the composite material. Unlike chemical or physical foaming, the air gaps introduced by this method are precisely limited to the sub-nanometer scale by the zeolite lattice, avoiding the precipitous decline in mechanical properties caused by micron-level bubble defects.

[0041] Compared to Examples 3-5, Comparative Example 1 showed a significant increase in dielectric loss, indicating that the modified cage-like silsesquioxane of this invention is the core component for suppressing dielectric loss. Unreacted carboxyl groups (-COOH) and hydroxyl groups (-OH) exist at the ends of the LCP molecular chain. Under a 10GHz high-frequency electric field, these polar end groups undergo secondary dipole relaxation, resulting in dielectric loss. The fluorinated graphene quantum dots in the modified cage-like silsesquioxane of this invention are rich in CF bonds at their edges, exhibiting extremely strong electronegativity. During melt processing, the CF bonds interact with the -OH / -COOH at the LCP chain ends to form quasi-hydrogen bonds, shielding and sealing the active end groups like a molecular cap. The POSS cage-like structure (1-2 nm) provides a physical barrier, blocking the cooperative coupling relaxation between the polar end groups of adjacent molecular chains, further suppressing the conversion of electromagnetic wave energy into thermal energy.

[0042] Meanwhile, in Comparative Example 2, the rate of change of Dk during humid heat aging increased, and the moisture resistance decreased significantly. The modified hexagonal boron nitride nanosheets exhibited both interfacial hydrophobicity and moisture resistance. The hydrophobic properties of the two-dimensional h-BN nanosheets and their layered orientation and stacking in the matrix extended the water vapor permeation path. The coupling agent formed a dense transition layer between the zeolite and LCP, preventing capillary condensation of liquid water at the sub-nanopore openings and allowing the air gaps within the pores to be retained in the water vapor environment.

[0043] II. Thermal Performance Testing Referring to GB / T1634.2-2019, the heat distortion temperature (HDT) of the composite material was determined using Method A with a bending stress of 1.80 MPa. The sample was placed in a silicone oil bath, a bending stress of 1.82 MPa was applied, and the temperature was increased at a rate of 2 °C / min. The temperature at which the deflection reached 0.34 mm was recorded. Referring to ASTM E1461, the thermal diffusivity of the composite material was tested using the laser flash method. A 25.4 mm × 1.0 mm disc was sprayed with a graphite coating, the lower surface was heated by a laser pulse, and the temperature rise curve of the upper surface was recorded by an infrared detector. The thermal diffusivity was then fitted. The melting temperature (Tm) of the composite material was determined using differential scanning calorimetry in a nitrogen atmosphere at a heating rate of 20 °C / min. The peak value of the second heating curve was recorded. Thermogravimetric analysis was used to determine the thermal weight loss temperature (Td5%) of the composite material in a nitrogen atmosphere at a heating rate of 20 °C / min. The temperature at which the mass loss reached 5% was recorded. The results are shown in Table 2 below.

[0044] Table 2 Test results of thermal properties of composite materials

[0045] As shown in Table 2, the planar thermal conductivity of Comparative Example 2 decreased significantly, proving that the modified hexagonal boron nitride nanosheets are the core for constructing the two-dimensional thermal conductivity network. h-BN nanosheets possess extremely high intrinsic in-plane thermal conductivity. In the injection molding shear flow field, the h-BN sheets are highly oriented and overlap each other along the flow direction, forming a quasi-continuous phonon transport network that penetrates the material. The zeolite nanoshuttles grown in situ on the h-BN surface act as rigid spacers, preventing the sheets from recombinizing due to van der Waals forces and maintaining the efficient dispersion of the single sheets. The zeolite crystals increase the contact area between the filler and LCP, and the coupling agent enhances the interfacial bonding, reducing phonon scattering loss at the interface.

[0046] III. Mechanical Property Testing Referring to GB / T1040.2-2022, the tensile strength of the composite material was tested using a Type I dumbbell-shaped specimen with a gauge length of 50 mm and a tensile rate of 5 mm / min. The stress-strain curve was recorded, and the tensile strength and tensile modulus were calculated. Referring to GB / T9341-2008, the flexural strength and flexural modulus of the composite material were tested using a span of 64 mm and a loading rate of 2 mm / min. The load-deflection curve was recorded, and the flexural strength and flexural modulus were calculated. Referring to GB / T1843-2008, the notched impact strength of the composite material was tested using the cantilever beam method. The specimen had a 2 mm deep V-notch, the pendulum energy was 2.75 J, the energy absorbed during fracture was recorded, and the notched impact strength was calculated. The results are shown in Table 3 below.

[0047] Table 3. Test results of mechanical properties of composite materials

[0048] As shown in Table 3, the tensile and flexural properties of Example 5 are stronger than those of Comparative Examples 1 and 2, indicating that the modified cage-like silsesquioxane and the modified hexagonal boron nitride nanosheets have a composite reinforcement effect. The modified hexagonal boron nitride nanosheets provide physical reinforcement. As a two-dimensional inorganic nanomaterial, the hexagonal boron nitride sheets themselves possess extremely high strength and modulus. In the injection molding shear flow field, these sheets are highly oriented along the tensile direction. When the material is subjected to tensile load, the stress is transferred from the liquid crystal polymer to the high-strength boron nitride sheets through the interface between the matrix and the filler. The sheets share a considerable portion of the load through the shear hysteresis effect, thereby improving the macroscopic load-bearing capacity of the composite material. The modified cage-like silsesquioxane provides crystallization reinforcement. The cage-like silsesquioxane induces the liquid crystal polymer to form more perfect extended-chain crystals, increasing the proportion of effective load-bearing structural units in the material. The extended-chain crystals of the liquid crystal polymer have extremely high theoretical strength and modulus along the molecular chain axis. Each increase in crystallinity means more high-strength crystalline regions participate in bearing external loads.

[0049] The notched impact strength monotonically decreases with increasing content of rigid filler (modified hexagonal boron nitride nanosheets). Both hexagonal boron nitride sheets and zeolite crystals are essentially rigid inorganic fillers, exhibiting a significant modulus difference with the liquid crystal polymer matrix. When the material is subjected to high-speed impact loads, the crack front encounters these rigid particles during propagation. Since the filler itself cannot absorb impact energy through significant deformation like a rubber-toughening phase, it instead induces a severe stress concentration effect at the interface. This stress concentration allows cracks to initiate and propagate at lower energy levels, ultimately resulting in a decrease in impact strength. The reason Comparative Example 2 exhibits the highest impact strength is precisely because it lacks rigid particles disrupting the matrix continuity; crack propagation requires traversing continuous resin regions, consuming more energy. Example 3 has the lowest filler content and larger particle spacing, allowing sufficient space for plastic deformation to dissipate energy during impact, thus maintaining acceptable toughness. However, when the filler content increases to the levels of Example 5 or even Example 4, the particle spacing decreases, stress fields superimpose, and the matrix's plastic deformation capacity is severely suppressed, leading to a significant deterioration in impact toughness.

[0050] IV. Processing performance and microstructure testing Referring to GB / T3682.1-2018, the melt volumetric flow rate (MVR) of the composite material was tested using a melt flow indexer. Preheating was performed at 330℃ for 5 min, with a load of 5.0 kg. The piston displacement was recorded, and the MVR (cm) was calculated. 3 (10 min); The microstructure of the cross section was observed using a scanning electron microscope. The sample underwent liquid nitrogen brittle fracture, and the cross section was sputtered with gold to observe the dispersion state and orientation degree of the filler. The crystallinity of LCP was analyzed by X-ray diffraction (XRD). The results are shown in Table 4 below.

[0051] Table 4. Results of Processing Properties and Microstructure Testing of Composite Materials

[0052] As can be seen from the data in Table 4, the melt volumetric flow rate (MVR) decreases with increasing rigid filler content (viscosity increases). The two-dimensional h-BN sheets have a large hydrodynamic volume in the flow field, which hinders the movement of LCP molecular chains. The hyperbranched polyester polyol processing aid acts as a ball bearing between molecular chains and can form a lubricating film on the mold wall, effectively suppressing the melt fracture phenomenon of LCP.

[0053] In Examples 3 and 5, the h-BN sheets are highly oriented along the flow direction and are uniformly dispersed. Zeolite crystals are firmly attached to the sheet surface without micron-level agglomeration, indicating that ball milling pretreatment and coupling agent modification ensure excellent dispersibility. In Example 4, the increased filler content led to localized stacking and aggregation of h-BN sheets, with uneven sheet spacing. The excessively high filler content increased the difficulty of dispersion, explaining the further decrease in impact strength and flowability.

[0054] XRD crystallinity of Example 5 > Comparative Example 1 > Comparative Example 2. Combined with heat distortion temperature (HDT) and thermal stability data, it can be seen that the modified cage-like silsesquioxane improves the heat resistance of the material through induced crystallization. The POSS nanocage structure in the modified cage-like silsesquioxane acts as a nucleating agent during melt cooling, lowering the free energy barrier for LCP crystallization and promoting the formation of more complete extended chain crystals. Increased crystallinity means a decrease in the proportion of amorphous regions. The amorphous region is the first region to soften at high temperatures; its reduction directly manifests as an increase in HDT. Simultaneously, due to the more compact molecular chain arrangement, the thermal decomposition temperature also slightly increases.

[0055] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0056] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A low-dielectric-value, low-loss liquid crystal polymer composite material, characterized in that, The raw materials include the following parts by weight: 90-110 parts of LCP resin, 0.5-1.5 parts of modified cage-type silsesquioxane, 5-7 parts of modified hexagonal boron nitride nanosheets, 0.1-0.5 parts of antioxidant, 0.1-0.5 parts of lubricant, and 0.1-0.5 parts of coupling agent; The modified cage-like silsesquioxane is an octaaminophenyl POSS surface grafted with fluorinated graphene quantum dots via a click chemical reaction. The modified hexagonal boron nitride nanosheets are pure silicon MFI-type zeolite nanoshuttles grown in situ via hydrothermal method after hydroxylation of hexagonal boron nitride nanosheets.

2. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 1, characterized in that, The LCP resin is a thermotropic aromatic liquid crystal polymer, which is a copolymer of p-hydroxybenzoic acid, terephthalic acid, or hydroquinone.

3. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 1, characterized in that, The antioxidant is an aromatic phosphite, the lubricant is a hyperbranched polyester polyol, and the coupling agent is an epoxy silane oligomer.

4. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 1, characterized in that, The preparation method of the modified cage-type silsesquioxane includes the following steps: (1) Under ice bath conditions, octaphenyl POSS was slowly added to a mixture of nitric acid and formic acid and stirred at room temperature for 18-22 h. The reaction solution was poured into ice water to precipitate the precipitate. The precipitate was filtered and washed with water until neutral to obtain octanitrophenyl POSS. The obtained octanitrophenyl POSS was then dissolved in tetrahydrofuran, Pd / C catalyst was added, H2 was introduced, and the mixture was stirred at 50 °C for 10-14 h. The Pd / C catalyst was removed by filtration, and the tetrahydrofuran was removed by rotary evaporation of the filtrate to obtain octaaminophenyl POSS. (2) A platinum mesh coated with fluorinated graphite was used as the cathode and a platinum wire as the anode. It was immersed in 100 mL of 0.1 M tetrabutylammonium tetrafluoroborate in acetonitrile solution and a constant potential of -2.5 V to -3.0 V (vsAg / AgCl) was applied for 3 to 5 h until the fluorinated graphite layer separated and the solution turned black. The sloughed suspension was placed in an ice bath and ultrasonically treated for 3 to 5 h. Large particles were first removed by filtration with a 220 nm filter membrane and then dialyzed with a 3500 Da dialysis bag for 46 to 50 h. The filtrate was freeze-dried to obtain fluorinated graphene quantum dots. (3) Fluorinated graphene quantum dots were ultrasonically dispersed in deionized water, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added. The mixture was ultrasonically activated at room temperature for 20-40 min. Octaaminophenyl POSS was dissolved in dimethyl sulfoxide and slowly added dropwise to the above fluorinated graphene quantum dot activation solution. The mixture was protected with N2 and magnetically stirred at 60°C for 22-26 h. After the reaction was completed, the reaction solution was added dropwise to anhydrous ethanol. The precipitate was collected by centrifugation and washed 1-3 times with N,N-dimethylformamide and acetone in sequence. The modified cage-like silsesquioxane was obtained by vacuum drying.

5. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 4, characterized in that, The volume ratio of nitric acid to formic acid in the mixed acid solution is 2:1, and the ratio of octaphenyl POSS to the mixed acid solution is 1g:10~20mL.

6. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 4, characterized in that, The mass ratio of the fluorinated graphene quantum dots, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and octaaminophenyl POSS is 1:0.5:0.3:

2.

7. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 1, characterized in that, The preparation method of the modified hexagonal boron nitride nanosheets includes the following steps: A. Add hexagonal boron nitride nanosheets and urea to deionized water, stir evenly, transfer to a planetary ball mill jar and ball mill for 10-14 hours, dilute the ball mill slurry, centrifuge at 1500 r / min at low speed to remove large particles that have not been peeled off, centrifuge the supernatant at 10000 r / min at high speed, collect the bottom precipitate, and freeze dry to obtain hydroxylated hexagonal boron nitride. B. Take hydroxylated hexagonal boron nitride and ultrasonically disperse it in deionized water. Stir tetraethyl orthosilicate, tetrapropylammonium hydroxide aqueous solution, anhydrous ethanol and deionized water to mix evenly to obtain a precursor sol. Slowly drop the prepared precursor sol into the hydroxylated hexagonal boron nitride dispersion and stir and age at room temperature for 4~8 hours. C. The mixture was transferred to a high-pressure reactor with a polytetrafluoroethylene liner. It was first kept at 80℃ for 22-26 hours, and then the temperature was raised to 170℃ for crystallization for 46-50 hours. After the reactor cooled naturally, the product was washed three times by centrifugation with deionized water, dried at 80℃, and then placed in a muffle furnace and calcined at 550℃ in air for 4-8 hours to obtain modified hexagonal boron nitride nanosheets.

8. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 7, characterized in that, The mass ratio of the hexagonal boron nitride nanosheets to urea is 1:2~3.

9. The low-dielectric-loss, low-loss liquid crystal polymer composite material according to claim 7, characterized in that, The molar ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide, ethanol and deionized water in the precursor sol is 1:0.35:20:4, and the ratio of hydroxylated hexagonal boron nitride to the precursor sol is 1g:140~160mL.

10. The method for preparing the low-dielectric-loss, low-loss liquid crystal polymer composite material according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1. Modified cage-type silsesquioxane and modified hexagonal boron nitride nanosheets were mixed with LCP ultrafine powder and anhydrous ethanol, respectively, and ball-milled at a low speed of 300 r / min for 2-4 h. The mixtures were then removed and dried to obtain the corresponding pre-dispersions. S2. Premix the two predispersants with LCP resin in a low-speed mixer for 4-6 minutes, add antioxidant, lubricant and coupling agent, and continue mixing until there are no white spots to obtain the mixture. S3. Add the mixture to a twin-screw extruder for melt extrusion. The twin-screw extruder speed is 300~350 r / min, the vacuum degree is -0.08 MPa, and the temperature is 300~330℃. After water cooling and drying, it is cut into cylindrical particles by a pelletizer to obtain modified LCP particles. S4. The modified LCP granules are dried in a dehumidifying dryer at 150℃ for 3~5h, and then injection molded by an injection molding machine with a barrel temperature of 310~330℃, a mold temperature of 120~150℃, a holding pressure of 40~60MPa for 3~5s, and then demolded at 110~120℃ to obtain the low dielectric and low loss liquid crystal polymer composite material.